Serological Investigation Of Caprine Brucellosis At Saniyah District - Mohsen Alrodhan (Kufa Journal for Veterinary Medical Sciences, 2017)
Brucellosis is important zoonotic disease in Iraq affect variety species of animals, cattle, sheep goats, camels and horses and transmitted to human being by direct contact with diseased animals or by ingestion of contaminated unpasteurized milk and milk products .The disease characterized by chronic nature and the infection may develop unobserved which lead to local clustering of infected cases. Serological survey was conducted to detect prevalence of brucella antibodies among goats by random selection of 120 animals in two villages at Saniyah out of target population of 848 in 32 villages. Rose Bengal test used for detection of IgM antibodies by using standard Brucella antigen ( Synbiotics,Lyon, France ), indirect ELISA kit ( NovaLisa, Germany) was applied to investigate the seroprevalence of brucellosis in goats of studied area, the results of collected serum samples which subjected to RBT & i ELISA were 10.8 % and 12.5 % respectively,the positive results of i ELISA were higher than that of RBT which was significantly differed .The seropositivty in male 20% were higher than female 12.17% with significant difference , while the seroprevalence in relation to age groups were reported in adult animals only 14.4% and 16.6 by using RBT and ELISA respectively and there were no positive results in young ones . In conclusion brucellosis is still spread among goats and host risk factor comprise age and sex in addition to the types of serological test influence the seroprevalence percentage, more attention should be directed towards preventing of caprine brucellosis by application of proper control programs.